Inventarisir Ragam Jajanan Khas Ternate dan Identifikasi Sumber Bahan Baku Pangan Lokal - Zasty Indriani; Rima Melati; Istikhara Istikhara; Humairoh Humairoh (Jurnal Pertanian Khairun, 2022)
ABSTRACTTernate local snacks have not been identified despite their potential as a business opportunity for MSMEs (micro, small, and medium enterprises) and farmers. This research aims to identify the numbers of Ternate local snacks and the utilization of raw materials from local foods. The research method used is surveys and interviews. Based on the research results, local snacks inventoried consist of 40 types of local snacks. The snacks are made from local food raw materials, such as cassava, banana, corn, sweet potato, pumpkin, breadfruit, and sago. The raw materials supplied from outside North Maluku region include sticky rice, rice, and flour. The percentage of the utilization of the snacks’ raw materials is cassava (17.50%), banana (15.00%), corn (7.50%), sweet potato and pumpkin (5.00%), and breadfruit and sago (2.50%). The information can be used to develop MSMEs’ business, culinary tourism, and arrangement of farmers’ planting pattern to produce commodities needed by consumers of snack producers, especially before and during the Ramadhan month.Keywords: Raw Materials, Snacks, Food, Local, Ternate